From fluorescence to biomass: A comprehensive analysis via crop modeling and sensing techniques - Georgios Ntakos; Egor Prikaziuk; Nastassia Vilfan; Tamme van der Wal; Christiaan van der Tol (Smart Agricultural Technology)
User-friendly handheld plant phenotyping devices, such as the MultispeQ, provide quick and easy measurements that effectively capture the dynamic nature of photosynthesis. This study demonstrates the added value of integrating measurements of such devices with both process-based and empirical modeling approaches for estimating the maximum leaf photosynthetic capacity (Amax) and biomass production (DMP) of potato crops. Utilizing leaf fluorescence measurements, such as the efficiency of photosystem II (ϕ2) and the electron transport rate, gathered from two fields in the Netherlands from May to September 2019, we determined the Amax to be 34 kg CO2 ha−1hr−1 with a standard deviation of 6.6 kg CO2 ha−1hr−1. By incorporating dynamic photosynthetic parameters, leaf area index (LAI) retrieval, and crop modeling techniques to scale assimilation from the leaf to the canopy level, we successfully reduced the discrepancy between simulated and measured dry matter production in 16 out of 18 cases, offering significant advantages over fixed, literature-based photosynthetic parameter values.